2016
DOI: 10.1016/j.apsusc.2016.03.196
|View full text |Cite
|
Sign up to set email alerts
|

Tuning surface porosity on vanadium surface by low energy He+ ion irradiation

Abstract: In the present study, we report on tuning the surface porosity on vanadium surfaces using highflux, low-energy He + ion irradiation as function of sample temperature. Polished, mirror-finished vanadium samples were irradiated with 100 eV He + ions at a constant ion-flux of 7.2  10 20 ions m-2 s-1 for 1 hour duration at constant sample temperatures in the wide range of 823-1173 K. Our results show that the surface porosity of V 2 O 5 (naturally oxidized vanadium porous structure, after taking out from UHV) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…Complementary to optical reflectivity, previous studies have demonstrated that ex situ XPS may be used to indirectly gain qualitative information on surface roughness and porosity. , , As surface roughness increases, the number of sites available for oxidation also increases. If a structured sample is then left to oxidize in ambient conditions before XPS is performed, the measurements should reveal a slightly larger contribution from Nb-oxide state(s) rather than pure Nb for the structured sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary to optical reflectivity, previous studies have demonstrated that ex situ XPS may be used to indirectly gain qualitative information on surface roughness and porosity. , , As surface roughness increases, the number of sites available for oxidation also increases. If a structured sample is then left to oxidize in ambient conditions before XPS is performed, the measurements should reveal a slightly larger contribution from Nb-oxide state(s) rather than pure Nb for the structured sample.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, our previous studies with other refractory metals clearly suggest similar trends between increasing surface feature size with increasing temperature during irradiation. 26,41,43,45 While bubble rupture provides a source of roughening and material migration to the surface, the mechanisms involved in the protrusion of fine tendril structures is still not entirely understood. Surface pores are typically observed as a precursor to the formation of fuzz, 63 suggesting that subsurface bubbles play a crucial role in surface structure formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mo also possesses a higher specific heat of vaporization, which will result in less evaporation during transient heat loading 30 . Fuzz formation has been shown to occur on both W and Mo, as well as other refractory metals, for certain fluence regimes and temperature windows 22 , 23 , 27 , 28 , 32 , 33 . Recent work has estimated a temperature window for W of 1000–2000 K, and a lower and narrower temperature window for Mo of 823–1073 K 23 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few preliminary studies investigating the response of these alternative refractory metals to high fluxes of He and H isotopes. It has been shown that under these similar He + ion irradiation conditions, significant nanostructuring is also observed in most other refractory metals such as molybdenum (Mo)1819, niobium (Nb)20, and vanadium (V)21. However, similar preliminary temperature-dependent studies in Ta22 show that Ta does not form the same high aspect ratio surface structures as observed in W, Mo, Nb, and V; rather, Ta only forms shallow surface pores when irradiated with high-flux, low-energy He + ion irradiation.…”
mentioning
confidence: 99%